Pengaruh Penilaian Esai Terhadap Pencapaian Kompetensi Siswa Pada Pembelajaran IPA: Tinjauan Pustaka - Fleony Dea Amanda; Utari Prisma Dewi; Fatni Mufit; Festiyed Festiyed (Postgraduate, University of Mataram, 2023)
The low scores of Pisa and TIMSS Indonesia show that students' abilities are still weak in 3 categories, namely linguistic literacy, scientific literacy, and mathematical literacy. To measure how far the achievement of student competence can be used assessment essay. Therefore this study aims to see the effect of essay assessment on students' competency achievement in science learning. This study used the literature review method through searches on Google Scholar and ERIC with the keywords